Regional and Cellular Mapping of Sortilin Immunoreactivity in Adult Human Brain - Xu, Shu-Yin; Zhang, Qi-Lei; Zhang, Qi; Wan, Lily; Jiang, Juan; Tu, Tian; Manavis, Jim; Pan, Aihua; Cai, Yan; Yan, Xiao-Xin (Frontiers in Neuroanatomy, 2019)
Sortilin is a member of the vacuolar protein sorting 10 protein (VPS10P) domain receptor family, which carries out signal transduction and protein transport in cells. Sortilin serves as the third, G-protein uncoupled, receptor of neurotensin that can modulate various brain functions. More recent data indicate an involvement of sortilin in mood disorders, dementia and Alzheimer-type neuropathology. However, data regarding the normal pattern of regional and cellular expression of sortilin in the human brain are not available to date. Using postmortem adult human brains free of neuropathology, the current study determined sortilin immunoreactivity (IR) across the entire brain. Sortilin IR was broadly present in the cerebrum and subcortical structures, localizing to neurons in the somatodendritic compartment, but not to glial cells. In the cerebrum, sortilin IR exhibited differential regional and laminar patterns, with pyramidal, multipolar and polymorphic neurons in cortical layers II-VI, hippocampal formation and amygdaloid complex more distinctly labeled relative to GABAergic interneurons. In the striatum and thalamus, numerous small-to-medium sized neurons showed light IR, with a small group of large sized neurons heavily labeled. In the midbrain and brainstem, sortilin IR was distinct in neurons at the relay centers of descending and ascending neuroanatomical pathways. Dopaminergic neurons in the substantia nigra, cholinergic neurons in the basal nuclei of Meynert and noradrenergic neurons in the locus coeruleus co-expressed strong sortilin IR in double immunofluorescence. In comparison, sortilin IR was weak in the olfactory bulb and cerebellar cortex, with the mitral and Purkinje cells barely visualized. A quantitative analysis was carried out in the lateral, basolateral and basomedial nuclei of the amygdaloid complex, as well as cortical layers II-VI, which established a positive correlation between the somal size and the intensity of sortilin IR among labeled neurons. Together, the present study demonstrates a predominantly neuronal expression of sortilin in the human brain with substantial regional and cell-type variability. The enriched expression of sortilin in pyramidal, dopaminergic, noradrenergic and cholinergic neurons suggests that this protein may be particularly required for signal transduction, protein trafficking and metabolic homeostasis in populations of relatively large-sized projective neurons.